2013
DOI: 10.1530/eje-12-1083
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen years of GH replacement improves body composition and cardiovascular risk factors

Abstract: ObjectiveFew studies have determined the effects of more than 5–10 years of GH replacement in adults on body composition and cardiovascular risk factors.Design/patientsIn this prospective, single-center, open-label study, the effects of 15 years of GH replacement on body composition and cardiovascular risk factors were determined in 156 hypopituitary adults (93 men) with adult-onset GH deficiency (GHD). Mean age was 50.5 (range 22–74) years at study start. Body composition was measured using dual-energy X-ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
3
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 42 publications
5
57
3
9
Order By: Relevance
“…GHD patients usually have decreased HDL and increased LDL cholesterol, as we found in our study, and the beneficial effects of GHT have been well documented, although a limitation of most studies is the lack of data concerning lipid-lowering treatment or the chronic use of these [35]. Our data, showing an improvement in total and HDL cholesterol in patients not receiving specific treatment, are in agreement with a series of studies which have confirmed that long-term GHT leads to a significant improvement in lipid profile [41], although other studies did not report any significant effect [42,43]. In addition, the neutral effect of GHD and GHT on triglycerides observed in our study is in agreement with the meta analysis performed by Maison et al [30].…”
Section: Discussionsupporting
confidence: 92%
“…GHD patients usually have decreased HDL and increased LDL cholesterol, as we found in our study, and the beneficial effects of GHT have been well documented, although a limitation of most studies is the lack of data concerning lipid-lowering treatment or the chronic use of these [35]. Our data, showing an improvement in total and HDL cholesterol in patients not receiving specific treatment, are in agreement with a series of studies which have confirmed that long-term GHT leads to a significant improvement in lipid profile [41], although other studies did not report any significant effect [42,43]. In addition, the neutral effect of GHD and GHT on triglycerides observed in our study is in agreement with the meta analysis performed by Maison et al [30].…”
Section: Discussionsupporting
confidence: 92%
“…There are no specific guidelines regarding the observation time needed in children treated for non-malignant CNS tumors such as craniopharyngioma (56). Over the past two decades, the use of hGH has been extended to GH-deficient adults, given the possible benefits on lipids, bone mass, body composition and quality of life (61,62). However, there are no studies demonstrating a lasting benefit of treating GHD specifically in adult CCS (12).…”
Section: Diagnosis and Managementmentioning
confidence: 99%
“…The majority of studies have displayed results for GH treatment for 2e3 years, and only a few studies dealt with the results for longer-term follow-up. In a study reporting on results of GH replacement for 15 years it was shown that the improvement in LBM was sustained while the FM returned to the levels the patients had at start of GH treatment [34]. Muscle mass, muscle strength and physical capacity increase [35] and the heart function improve [36].…”
Section: Body Composition and Bone Healthmentioning
confidence: 99%